Exploring multiple levels of suffering and suicide prevention in an era of emerging national legislations - Goldblatt, Mark; Castelli Dransart, Dolores Angela; Lapierre, Sylvie; Waern, Margda; Lindner, Reinhard (Frontiers in Public Health, 2025)
Access to assisted dying (variously called assisted suicide, euthanasia, and medical aid/assistance in dying) is increasingly available in many countries around the world. Individual suffering in the present and fears for the future, feature prominently in the request for assisted dying, which then affects many people beyond the identified individual, including family and loved ones, the clinical team associated with the dying process and societies. We consider expanding waves of distress, beginning with the subjective intrapsychic suffering of the individual requesting assistance in dying, the interpersonal effect on survivors, and the complex responses in those facing requests for assisted death. The autonomous rights of the individual to the alleviation of suffering are balanced by efforts toward suicide prevention, which are impacted when there are limited options to alleviate the psychosocial and existential suffering of those who express the wish to die.